2015
DOI: 10.1139/cgj-2013-0476
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the behaviour of coal wash and steel slag mixtures under triaxial conditions

Abstract: The effective reuse and recycling of granular waste materials, namely coal wash (CW) and Basic Oxygen Steel slag (BOS), is economically beneficial and environmentally sustainable. Nevertheless, due to the heterogeneity of these granular waste materials, their ultimate adoption as structural fills must be supported by constitutive relationships capable of accurately describing the stress-strain behaviour under representative field loading conditions. In this paper, a critical-state-surface generalised-plasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…With those specimens on the dry side of CSL, there was dilative behaviour in volumetric strain and peak-softening in stress-strain, and with the specimen on the wet side of CSL, there was volumetric contraction and hardening in deviatoric stress. This behaviour was similar to that reported by a number of previous studies on the behaviour of granular material, for instance, as discussed by Indraratna et al, (1998), Modoni andGazzellone, (2011), andChiaro et al, 2014a. Figure 5 illustrates the typical stress-strain behaviour of all the mixtures under effective confining pressures of 30kPa and 120kPa, and it was evident that the CW content had a significant influence on the shear behaviour.…”
Section: Stress-strain Behavioursupporting
confidence: 88%
“…With those specimens on the dry side of CSL, there was dilative behaviour in volumetric strain and peak-softening in stress-strain, and with the specimen on the wet side of CSL, there was volumetric contraction and hardening in deviatoric stress. This behaviour was similar to that reported by a number of previous studies on the behaviour of granular material, for instance, as discussed by Indraratna et al, (1998), Modoni andGazzellone, (2011), andChiaro et al, 2014a. Figure 5 illustrates the typical stress-strain behaviour of all the mixtures under effective confining pressures of 30kPa and 120kPa, and it was evident that the CW content had a significant influence on the shear behaviour.…”
Section: Stress-strain Behavioursupporting
confidence: 88%
“…void ratio vs mean effective stress) due to particle degradation. Chiaro et al (2015) found that the CSL for SFS+CW blends was not unique and was sensitive to the mix proportions and the extent of grain degradation upon loading. In view of the abovementioned reasons, experimental observations from past studies conducted on soil-rubber chips/fibre mixtures or traditional granular soils such as sands cannot be extrapolated to interpret or predict the behaviour of the current SFS+CW+RC matrix.…”
Section: Introductionmentioning
confidence: 97%
“…Leventhal, 1996;Okagbue and Ochulor, 2007;Rujikiatkamjorn et al, 2013;Heitor et al 2016), coal tailings (e.g. Indraratna et al, 1994;Williams et al, 1995;Morris and Williams, 1997;Williams and King, 2016) and mixtures of coal wash and other waste materials like steel furnace slag and rubber crumbs (Chiaro et al, 2014, Indraratna et al, 2018Qi et al, 2018, Indraratna et al, 2019 was studied widely in the literature. Some of these studies have demonstrated that marginal materials like coal wash have acceptable geotechnical properties to be used as a construction fill in port reclamation projects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have demonstrated that marginal materials like coal wash have acceptable geotechnical properties to be used as a construction fill in port reclamation projects (e.g. Rujikiatkamjorn et al, 2013;Chiaro et al, 2014, Tasalloti et al, 2015 or as a subballast layer in railways (Indraratna et al, 2018). However, the reuse of coal wash as base/subbase material in pavement construction has not been systematically explored in past studies on waste materials.…”
Section: Introductionmentioning
confidence: 99%